Academic Faculty Wives and Systemic Discrimination —Antinepotism and "Inbreeding" - Dagg, Anne Innis (Canadian Journal of Higher Education, 1993)
In the past, the academic careers of women married to professors have often been disadvantaged by anti-nepotism rules in universities and by informal department policies against hiring one's own Ph.D. graduates. To determine if these two systemic forms of discrimination, which especially affect faculty wives, are still operating, a study was made at a large university, the University of Waterloo. UW calendars show that some departments have hired academic spouses and many have hired their own Ph.D.s; however, a survey of UW professors indicates that a sizable number are against hiring spouses in a department and against a department hiring its own Ph.D.s. There is still cause for concern, therefore, if a university wants to hire the best candidate for a position and she happens to be a faculty wife.